China's Peaceful Development: A Responsible Great Power or a Good Neighbour? - Ramadhani, Eryan (The Sunan Ampel Review of Political and Social Sciences, 2022)
The rise of China has become a catchword to define China’s current position in the international system. China’s increasing power comes with responsibility. Continuing Hu Jintao’s peaceful development, Xi Jinping is committed to realising China’s responsibility as a great power. Concurrently, Xi sets out a neighbourhood diplomacy that underlines the importance of bringing development and prosperity to neighbouring states. This paper aims to investigate the way China realise the twin goals of peaceful development. The South China Sea (SCS) disputes involving China and four neighbouring Southeast Asian states serves as a case study. It is found that China's assertiveness, manifested in continued escalations and dragged-on negotiations on the Code of Conduct (COC), does not bode well for China’s peaceful development. In other words, China is hardly a responsible great power or a good neighbour in its handling of the SCS issue.